(untitled) (Baghdad Science Journal, 2025)
The electrical properties of polycrystalline cadmium telluride thin films of different thickness (200,300,400)nm deposited by thermal evaporation onto glass substrates at room temperature and treated at different annealing temperature (373, 423, 473) K are reported. Conductivity measurements have been showed that the conductivity increases from 5.69X10-5 to 0.0011, 0.0001 (?.cm)-1 when the film thickness and annealing temperature increase respectively. This increasing in ?d.c due to increasing the carrier concentration which result from the excess free Te in these films.